Sounding Extremes: Ecological Sound Art in the Anthropocene - Barclay, Leah (Circuit)

(untitled) (Circuit, musiques contemporaines, 2022)
The catastrophic impacts of climate change, vanishing biodiversity, and the rapid deterioration of our global ecosystems require urgent attention and aggressive political action. This article explores a body of interdisciplinary research through a series of ecological sound projects designed to draw attention and awareness to changing ecosystems. These projects are framed as participatory acoustic ecology and position the discipline as a socially engaged, inclusive, accessible, interdisciplinary field that inspires communities to listen and act during times of crisis.